Ideas: Tell me what you eat, and I’ll tell you who you are - Gustavo Laborde (The UNESCO Courier, 2022)
The act of eating is governed by a principle of absorption. The food we ingest has concrete biochemical effects in the body. This is why we literally are what we eat. But this aphorism also works the other way round – we eat what we are. Because, when we eat, we absorb not only nutrients, but also symbols and meanings. All cultures assign specific meanings to their foods – there are everyday dishes and festive dishes, main meals and snacks, things that are eaten and things that are not. Food not only weaves a web of meanings, it is also a central feature of collective and individual identities.